Analysis of superficial mycoses in children examined in 2013–2016 in the Unit of Medical Mycology at the Department of Dermatology, Poznan University of Medical Sciences - Browicz, Anna; Kubisiak-Rzepczyk, Honorata; Hasse-Cieślińska, Marta; Karasińska, Aneta; Adamski, Zygmunt (Dermatology Review/Przegląd Dermatologiczny, 2017)
Introduction. The superficial mycoses remain a group of diseases of public health significance. The increased incidence of mycoses is related, among other factors, to deficiency of the immune system, coexisting systemic and dermatological diseases, long-term, non-target antibiotic therapy and the increase in the number of people at risk of immunosuppression. Objective. To analyze the etiology and epidemiology of mycosis in patients under 18 years of age in the years 2013–2016 diagnosed in the Unit of Medical Mycology at the Department of Dermatology, Poznan University of Medical Sciences. Material and methods . A retrospective, etiological and epidemiological analysis was performed on the incidence of superficial mycosis in 295 patients under 18 years of age diagnosed in the years 2013–2016 in the Unit of Medical Mycology at the Department of Dermatology, Poznan University of Medical Sciences. Results . The study group included mostly cases of dermatophytic superficial mycosis of the scalp with prevalent zoophilic species, including Microsporum canis as the most common. Conclusions. Superficial mycoses are common during childhood. Increased incidence of certain forms of superficial mycoses in children has been observed, for example infections transmitted from exotic animals or onychomycosis.